Patient Safety Culture in a Tunisian Teaching Tertiary Care Hospital - Mohamed Ben Rejeb; Dhekra Chebil; Latifa Merzougui; Balsem Kacem; Selwa Khefacha-Aissa; Lamine Dhidah; Houyem Said- Laatiri (Archives of Nursing Practice and Care - Peertechz Publications, 2017)
Objectives: Our study aimed to investigate patient safety attitudes and perceptions amongst health care providers in Tunisian tertiary care hospitals. Methods: This cross-sectional study was conducted during April May and June 2015 in Sahloul  University hospital in Sousse: a 630-beds tertiary hospital in Eastern Tunisia. This survey included 344 cares providers. The French version of the Hospital Survey on Patient Safety Culture questionnaire was used to identify dimensions of patient safety culture. Results: Areas with potential for improvement were overall perception of security, Teamwork within units, organizational learning/continuous improvement, open communication and underreporting of events.  Teamwork across hospital units had the lowest score. No signifi cant differences between physicians and nurses were found for all composites in our study. Conclusion: Patient safety culture remains underdeveloped in our hospital. Leaders must implement a development strategy by creating the culture and commitment needed to identify and solve underlying systemic causes related to patient safety.